Common Factors of Cost Escalation in Construction Industry of Pakistan - Ahmed, S.; Memon, A. H.; Memon, N. A.; Laghari, A. N.; Akhund, M. A.; Imad, H. U. (Engineering, Technology & Applied Science Research, 2018)
Cost escalation is a ubiquitous problem, especially in Government organizations. Though bigger projects encompass escalation cost, in smaller projects, it is generally ignored. Several internal and external factors are responsible for the undesirably increased cost of a project. Among them some are tangible, and some are intangible. The scope of this study is to highlight most common remittable and non-remittable factors responsible for cost escalations. Thirty most common factors responsible were listed. A survey was done in order to have the stakeholder’s opinion on identifying the most common factors. Out of 102 generally identified escalating factors, 30 factors were shortlisted based on literature and initial study. Participants responded on a 1 to 5 Likert’s scale. Out of 200 distributed questionnaires, 52 reliable set of questionnaires were selected for data analysis. Clients, consultants, and constructors were selected from different projects like roads, structure, public amenities etc. Minimum threshold to participate in the survey was that a respondent must had at least a Diploma or Bachelor’s degree in the field of civil engineering. Results highlighted that financial problems, slow payments, and inflation are the top-ranked identified factors responsible for cost escalation in the construction industry of Pakistan. The weighted average of all factors ranges between 0.355 and 0.688, having 0.668, 0.629 and 0.625 for the top three factors.